(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article provides an in-depth analysis of the motif of الفخر (al-Fakhr)—that is, self-exaltation and heroism—in the poetry of Abu at-Tayyib al-Mutanabbī, a prominent figure in 10th-century Arabic literature. The concept of individual honor and dignity, as well as the poetic expression of courage and personal power, is examined in a sociological and literary context. The article also scientifically substantiates the connection of the *fakhr* motif in al-Mutanabbi’s poetry with the value system of medieval Arab society and the relevance of this poetic tradition today.